2009
DOI: 10.1038/aps.2008.18
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the ipsilateral and contralateral cerebellum in the acquisition of unilateral classical eyeblink conditioning in guinea pigs

Abstract: Aim:The aim of this study was to evaluate the relative contributions of the ipsilateral and contralateral cerebellum to the acquisition of unilateral classical eyeblink conditioning (EBCC). Methods: The unilateral EBCC was achieved using a binaural tone conditioned stimulus (CS) paired with a left airpuff unconditioned stimulus (US). A high-resolution potentiometer was used to monitor eyeblink responses. Guinea pigs received one CS-US session followed by three CS-US sessions (sessions 2 to 4), during which mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…It has been shown that guinea pigs can generalize this response to other sound levels and to intracochlear electrical stimulation ( 17 , 19 ). Guinea pigs can also be trained to respond to pure tones, although in different training paradigms ( 21 25 ). In spite of these positive findings, training guinea pigs to respond to silent intervals (CS) in noise was unsuccessful, both in naïve and previously trained animals.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that guinea pigs can generalize this response to other sound levels and to intracochlear electrical stimulation ( 17 , 19 ). Guinea pigs can also be trained to respond to pure tones, although in different training paradigms ( 21 25 ). In spite of these positive findings, training guinea pigs to respond to silent intervals (CS) in noise was unsuccessful, both in naïve and previously trained animals.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, for optogenetic activation of the bilateral caudal mPFC and of its axon terminals in the PN, rats were bilaterally microinjected with 0.5 µL of pAAV 2/9-CaMKIIα-ChR2(H134R)-mCherry (Virus titers: 1.35 × 10 13 GC/mL) or pAAV 2/9-CaMKIIα-mCherry (Virus titers: 1.25 × 10 13 GC/mL) into both left and right caudal mPFC (AP + 1.92 mm, ML ± 0.9 mm, DV − 3.0 mm; Figs 3A,B and 5A,B). In addition, previous studies have shown that the mPFC projects bilaterally to the PN, which then projects predominantly to the contralateral cerebellum, and that only the ipsilateral cerebellum (relative to the US presented eye) is required for EBC (Hu et al 2009;Moya et al 2014). Thus, for direct optogenetic activation of the PN cell bodies, rats were unilaterally microinjected with 0.5 µL of pAAV 2/9-hSyn-ChR2(H134R)-mCherry (Virus titers: 5.18 × 10 12 GC/mL) or pAAV 2/9-hSyn-mCherry (Virus titers: 7.04 × 10 12 GC/mL) into the right PN (AP −7.32 mm, ML 0.9 mm, DV −10.0 mm; i.e., contralateral to the training eye) (Fig.…”
Section: Virus Injectionmentioning
confidence: 99%